2013
DOI: 10.3109/09638288.2013.863392
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional model of optimal participation of children with physical disabilities

Abstract: Consideration of relevant child, family and environment determinants of dimensions of optimal participation should assist children, families and health care professionals to identify meaningful goals and outcomes and guide the selection and implementation of innovative therapy approaches and methods of service delivery. Implications for Rehabilitation Optimal participation is proposed to involve the dynamic interaction of physical, social and self-engagement and attributes of the child, family and environment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 71 publications
(106 reference statements)
2
56
0
1
Order By: Relevance
“…Participation is broadly conceptualized as “involvement in life situations” (10) within psychology and disability related literature, but ambiguity surrounds the intended meaning of the term (8, 9) as a measurable index of health relative to being physically active. Recent efforts to integrate this construct in health literature are exemplified by Kang and colleagues (11). For children who experience physical disabilities, they define optimal recreation and leisure participation as the quality of child–environment interactions reflected in individualized (objective and subjective) physical, social, and self-engagement outcome measures (p. 1735).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation is broadly conceptualized as “involvement in life situations” (10) within psychology and disability related literature, but ambiguity surrounds the intended meaning of the term (8, 9) as a measurable index of health relative to being physically active. Recent efforts to integrate this construct in health literature are exemplified by Kang and colleagues (11). For children who experience physical disabilities, they define optimal recreation and leisure participation as the quality of child–environment interactions reflected in individualized (objective and subjective) physical, social, and self-engagement outcome measures (p. 1735).…”
Section: Introductionmentioning
confidence: 99%
“…For children who experience physical disabilities, they define optimal recreation and leisure participation as the quality of child–environment interactions reflected in individualized (objective and subjective) physical, social, and self-engagement outcome measures (p. 1735). Kang et al (11) cautions against inferring poor health from observed differences in frequency and intensity of PA participation between disabled and non-disabled children, without consideration for quality of children’s experiences. Misperceptions about the extent to which a child can participate may result in fewer opportunities or expectations for disabled children and reduce engagement in this health-promoting behavior.…”
Section: Introductionmentioning
confidence: 99%
“…One of the online benefits for people with disabilities was argued by Bowker and Tuffin [94] to be enhanced choice over self-representation, which was also supported by Clarke et al [95] who found AAC technology supported participant perceptions of being able to say what they liked and tell jokes. One of the challenges faced by young adolescents who use AAC was identified by Tavares and Peixoto [96] shown reduced social participation opportunities for people with cerebral palsy [41][42][43][44][45][46]. Targeted intervention to support adolescents with physical disabilities to use the Internet and social media was shown by Raghavendra et al [9] to increase the number of online communication partners and offer new ways to extend social connections and Ellison et al [35] also found social media supported the maintenance of social ties.…”
Section: Consequencesmentioning
confidence: 99%
“…[96][97][98][99] The conceptual framework developed through an integrative review by Kanagasabai et al 100 suggests contextual conditions under which participation is reduced or maintained ( Figure 2). Another review, by Kang et al, 101 proposes that participation is optimised with physical, social and self-engagement. Social engagement refers to interpersonal interactions during activities, feelings of being included or belonging.…”
Section: Modelling Process: Developing Programme Theorymentioning
confidence: 99%
“…275 Alternative or supplementary patient-centred outcome assessments for such a study might include the measure yourself medical outcome profile. 276 The complexity of participation as a concept 98 and limitations with the ACTIVLIM 148 as a measure of participation have recently been pointed out; 277 researchers should agree dimensions of participation and corresponding validated instruments 101,227 in consultation with service users. Chapter 10 Conclusions A full-scale RCT based on frequentist methods is not feasible based on the trial protocol piloted in this study.…”
Section: Costs Borne By Patientsmentioning
confidence: 99%